Impact of blood group on survival following critical illness: a single-centre retrospective observational study. Issue 1 (29th June 2019) - Slade, Robert; Alikhan, Raza; Wise, Matt P; Germain, Lam; Stanworth, Simon; Morgan, Matt
Abstract : Background: Predicting patient outcomes following critical illness is challenging. Recent evidence has suggested that patients with blood group AB are more likely to survive following major cardiac surgery, and this is associated with a reduced number of blood transfusions. However, there are no current data to indicate whether a patient's blood group affects general intensive care outcomes. Objective: The objective of this study was to determine if ABO blood group affects survival in intensive care. The primary outcome measure was 90-day mortality with a secondary outcome measure of the percentage of patients receiving a blood transfusion. Design: Retrospective analysis of electronically collected intensive care data, blood group and transfusion data. Setting: General intensive care unit (ICU) of a major tertiary hospital with both medical and surgical patients. Patients: All patients admitted to ICU between 2006 and 2016 who had blood group data available. Intervention: None. Measurements and main results: 7340 patients were included in the study, blood group AB accounted for 3% (221), A 41% (3008), B 10.6% (775) and O 45.4% (3336). These values are similar to UK averages. Baseline characteristics between the groups were similar. Blood group AB had the greatest survival benefit (blood group AB 90-day survival estimate 76.75, 95% CI 72.89 to 80.61 with the overall estimate 72.07, 95% CI 71.31 to 72.82) (log-rank χ 2 16.128, p=0.001). Transfusion requirements were similar in all groups with no significant difference between the percentages of patients transfused (AB 23.1%, A 21.5%, B 18.7%, O 19.9%, Pearson χ 2 5.060 p=0.167). Conclusion: Although this is primarily a hypothesis generating study, intensive care patients with blood group AB appeared to have a higher 90-day survival compared with other blood groups. There was no correlation between blood group and percentage of patients receiving transfusion.